Research on Bionic Hierarchical Optimization of Wing Based on PLSR and PSO - ZHANG, Xiaoxin; WANG, Qi (Mechanika (Kaunas, Lithuania : 1995), 2023)
The layout of the wing's internal structure not only dramatically influences the wing's strength stiffness but also directly affects the aerodynamic characteristics of the aircraft. Based on the original wing structure, a more flexible spatial design layout to achieve improved overall structural load-bearing performance, and a reasonable structural lightweight design are the research priorities to be considered for the development of future aircraft. Therefore, this paper attempted to design and analyze a lightweight airfoil that meets the performance requirements. Combining the strategy of hierarchical optimization design with the advantages of engineering bionics, the diatom Arachnoidiscus bionic structure, topological optimization, partial least squares regression (PLSR), and multi-objective particle swarm algorithm (PSO) are applied to optimize the placement and size of wing’s internal components. The simulation results show that the weight of the optimized wing structure is reduced by 6% while satisfying the requirements of maximum stress and maximum deformation.